The Coming Together of Astronomy and Economics - Knapowski, Roch (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
The paper is an English translation of Skojarzenie się astronomii z ekonomią by Roch Knapowski published originally in Polish in Opuscula Casimiro Tymieniecki septuagenario dedicata in 1964. The text is published as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Faculty of Law and Ad-ministration” devoted to the achievements of the late Professors of the Faculty of Law and Administration of the Adam Mickiewicz University, Poznań.